2016
DOI: 10.1021/acs.jpcb.6b00997
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 8: Characterization of Physiological Divalent Metal Catalysis

Abstract: Histone deacetylases (HDACs) are responsible for the removal of acetyl groups from histones, resulting in gene silencing. Overexpression of HDACs is associated with cancer, and their inhibitors are of particular interest as chemotherapeutics. However, HDACs remain a target of mechanistic debate. HDAC class 8 is the most studied HDAC, and of particular importance due to its human oncological relevance. HDAC8 has traditionally been considered to be a Zn-dependent enzyme. However, recent experimental assays have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 77 publications
(157 reference statements)
0
31
0
Order By: Relevance
“…S1 in ESI † ). 16 Details on QM/DMD can be found elsewhere. 17 The largest active site models were determined by including any residue with at least one atom within 7 Å of the Zn 2+ ion.…”
Section: Computational Methods and Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…S1 in ESI † ). 16 Details on QM/DMD can be found elsewhere. 17 The largest active site models were determined by including any residue with at least one atom within 7 Å of the Zn 2+ ion.…”
Section: Computational Methods and Theorymentioning
confidence: 99%
“…1 to be the most viable. 16 Through this mechanism, H143 acts first as a base, abstracting a proton from the water molecule, and second as an acid, transferring the proton to the substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr(r) in the reactant states of related enzymes, for example designed computationally to catalyze the same reaction, serves as a probe of relative catalytic activity prior to the mechanistic study, as is shown here, and also was shown in a recent study of the metal-specificity in histone deacetylase. 96 This method is motivated by the Hammond postulate, which states that reaction barriers will be lower when the reactant state is ''similar'' to the transition state. The extensions to QTAIM used here provide a method for quantifying the similarity of reactant and transition states, through the amount of charge density at critical points that play an important role in the reaction coordinate. )…”
Section: Comparison Of Native Enzyme and V243r_fpepd In The Transitiomentioning
confidence: 99%
“…Molecular modeling in combination with electron-density analysis is already used for organic reaction studies. Equilibrium geometry congurations and corresponding calculated electron densities of reagents, intermediates, transition states and products of chemical reactions are analyzed by various approaches as QTAIM (Quantum Theory of Atoms in Molecules) [29][30][31][32][33][34][35][36][37][38][39][40][41] or conceptual DFT (Density Functional Theory) 23,36,[42][43][44] as well as diverse bonding descriptors. [33][34][35][36][37]45,46 Current studies of enzymatic reactions [47][48][49] also demonstrate an enhanced interest in the application of such combined methods in biochemistry.…”
Section: Introductionmentioning
confidence: 99%